The Research of Chaos-based M-ary Spreading Sequences - GAO Qiang; YAN Hua; YANG Hongye (Institute of Advanced Engineering and Science, 2012)
This paper is devoted to the generation and evaluation of the Chaos-based M-ary spreading sequences on communications systems. Sequences obtained by repeating a truncated and multi-ary quantized chaotic series are compared with classical m-sequences by means of the autocorrelation and cross-correlation properties and power-spectral features. Anti-noise performance of binary sequences and chaotic-based M-ary spreading sequences has been compared in the case of the same single-frequency interferences. Studies have shown that spectral features and anti-noise performance of chaotic-based M-ary spreading sequences which have great researching value are better than binary sequences. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1654